Chapter 1 Rachel Cusk The Expansive - Wittman, Emily O. (Taylor & Francis, 2021)
In The New Midlife Self-Writing, Wittman treats recent self-writing by Rachel Cusk, Roxane Gay, Sarah Manguso, and Maggie Nelson, carefully situating these vital midlife works within the history of self-writing. She argues that they renew and redirect the autobiographical trajectories characteristic of earlier self-writing by switching their orientation to face the future and by celebrating midlife as growing season, a time of Bildung. In each chapter, writer-by-writer, she demonstrates how the midlife self-writers in question trace confident and future-oriented paths through the past, rejecting triumphalism and complicating both identity and individualism, just as they refine and redefine genres. Exploring these midlife self-writers as chroniclers of Generation X's midlife in particular, Wittman coins the term "digital absence" to map their unique relationship to new forms of knowledge and knowledge gathering in an Information Age that they are both of and set apart from. She theorizes that their works share a "pedagogical style," a style characterized by clarity, exposition, and classical rhetoric, and a concern with the classroom, offering a warrant for reading them in pedagogical terms in concert with traditional scholarly approaches. Furthermore, Wittman presents readers with an overview of future midlife self-writing as well as self-writing overall, concluding that we might be looking at the scholarship of the future.